Ecosystem Readiness: Blockchain Adoption is Driven Externally - Lustenberger, Michael; Malešević , Saša; Spychiger, Florian (Frontiers in Blockchain, 2021)
Blockchain technology has been extensively tested, implemented, used, or even abandoned by organizations. Whether organizations adopt blockchain technology depends on many factors. Previous literature has identified a range of potential factors affecting the adoption of blockchain technology, but most studies have focused solely on a subset of specific factors. As a result, these studies can provide only limited explanations for the varying degrees of blockchain adoption. By relying on the well-established Technology-Organization-Environment (TOE) framework, we propose an extended Blockchain Adoption Model (BAM). We derive a rich set of factors from the current state of research on blockchain adoption and the business ecosystem literature and extend them by conceptual reasoning. We then develop testable hypotheses for each of the identified factors. The resulting 14 hypotheses are tested by conducting a survey (n = 350) within the DACH-region (Germany, Austria and Switzerland). We quantitatively analyze our BAM with a binary logistic regression analysis and identify six constructs impacting the adoption (relative advantage, observability, organizational age, external stakeholder pressure, regulatory uncertainty, and scope of business ecosystem). Based on our findings we introduce the novel idea of 'ecosystem readiness' as the most important factor for the adoption of blockchain. Ecosystem readiness is characterized by the following attributes: (1) a large ecosystem scope, (2) stakeholders that are not yet collaborating in a trustful and regulated environment, and (3) a powerful organization leading the ecosystem. This powerful organization further intentionally promotes innovation by (4) making the benefits of this new technology observable for others, by (5) putting pressure on the other ecosystem participants to adopt the new technology, and eventually by (6) striving for regulatory certainty in the application and use of blockchain.